A new PD(1+PI) direct power controller for the variable-speed multi-rotor wind power system driven doubly-fed asynchronous generator. (November 2022) - Benbouhenni, Habib; Bounadja, Elhadj; Gasmi, Hamza; Bizon, Nicu; Colak, Ilhami
Abstract: This paper presents a novel direct power control (DPC) based both on proportional–derivative and proportional–integral regulators (PD (1+PI)) with a simplified space vector modulation (SSVM) strategy for variable-speed multi-rotor wind turbine (VSMRWT) driven doubly-fed asynchronous generator (DFAG) without phase-locked loop (PLL). The proposed control, called DPC-PD(1+PI), is designed to reduces the active and reactive powers ripples and improve the current quality. The combination of PD and PI controllers is the principle of the designed DPC technique. The main advantage of this method is that the ripples of the active and reactive powers and the current harmonic distortion, which represents the major disadvantages of the conventional direct power control scheme, are more minimized. Furthermore, this technique achieves a high current quality, reduce the steady-state error of the active and reactive powers, and improve the response dynamic of the generator. The behavior of the designed strategy compared to the conventional direct power control in several different tests such as the random wind speed behavior, change of generator parameters, and variable demand for active power are the mainly aims of this study. A numerical simulation by Matlab software is achieved to confirm the validity of the proposed direct power control approach for a 1.5 MW DFAG-based VSMRWT. The simulation results showed that the designed direct power control scheme is better than the conventional direct power control scheme in terms of improving response dynamic, minimization of harmonic distortion of current (50.24%) and significant minimization of ripples of reactive power (47.50%) and active power (46.68%). Also, the designed direct power control scheme is very robust for random variations in the reference order and parametric changes of the generator.